(untitled) (Philological Studies, 2019)
The article presents an analysis of masculine and feminine nouns denoting professions in English and Slovenian. The researched expressions are first discussed from the point of view of word-formation (derivation and compounding), then corpora are employed to examine the frequency of the forms in both languages. The corpus data are complemented with an analysis of collocators with the purpose of identifying the semantic preferences and associative meanings of gender-marked expressions for professions. The results reveal that some feminine nouns for professions are stylistically unmarked (especially in Slovenian), whereas others co- occur (in English and Slovenian) with words that reflect the societal attitudes to gender roles, appearance and character.